Indicative of developmental coordination disorder in students aged between 7 to 10 years Indicativo de transtorno do desenvolvimento da coordenação de escolares com idade entre 7 e 10 anos - Da Silva J.* (2013)
The objective of this study was to characterize the participants of both sexes, aged between 7 and 10 years, regarding to the presence of the Developmental Coordination Disorder - DCD. A group of 406 children aged between 7 to 10 years old, being 231 girls and 175 boys from a public school in São José/SC participated of this study. The motor assessments and indicative of DCD were made according to the Movement Assessment Battery for Children - First Edition (MABC-1; HENDERSON; SUGDEN, 1992). The prevalence of the indicative of DCD was 11,1%, value considered high when compared to reports of international researchs, but similar to the percentage found in other Brazilian studies.